A three-order-parameter bistable magnetoelectric multiferroic metal - Andrea Urru; Francesco Ricci; Alessio Filippetti; Jorge Íñiguez; Vincenzo Fiorentini (Nature Communications, 2020)
A room temperature single-phase multiferroic with large and strongly coupled polarization and magnetization is a long-sought goal in multiferroics research. Here, the authors predict a promising candidate, layered-perovskite metal Bi5Mn5O17, which is a ferromagnet, ferroelectric, and ferrotoroid.